'Fluctuations of life': mutability and impermanence in Aleksandr Petrov's animated films. (4th May 2021) - Mihailova, Mihaela
ABSTRACT: This article focuses on Russian animation director Aleksandr Petrov's short films, created with the rarely employed, labour-intensive paint-on-glass technique. Using an animation studies approach, this article explores the formal features of Petrov's signature aesthetic, often described as 'painting brought to life'. In particular, this discussion of his oeuvre focuses on the ways in which his animation technique facilitates the complex interplay between visual metamorphosis, spatial mutability and temporal ellipsis characteristic of his films. Through a close reading of relevant sequences from a range of works (including both fictional and promotional shorts), this article investigates how the constant metamorphic flow of the director's imagery engenders what Petrov himself has described as 'the sense of instability and fluctuation of life' that permeates his animation. In doing so, it aims to suggest that paint-on-glass films – and under-camera animation more broadly – can challenge and complicate existing assumptions about animation and destabilise traditional hierarchies in film theory discourse.